Individualized closed-loop TMS synchronized with exoskeleton for modulation of cortical-excitability in patients with stroke: a proof-of-concept study - Singh, Neha; Saini, Megha; Kumar, Nand; Padma Srivastava, M. V.; Mehndiratta, Amit (Frontiers in Neuroscience, 2023)
Background: Repetitive TMS is used in stroke rehabilitation with predefined passive low and high-frequency stimulation. Brain State-Dependent Stimulation (BSDS) / Activity-Dependent Stimulation (ADS) using its bio-signal has been observed to strengthen synaptic connections. Without the personalization of brain-stimulation protocols, we risk a one-size-fits-all approach. Methods: We attempted to close the ADS loop via intrinsic-proprioceptive (via exoskeleton-movement) & extrinsic-visual-feedback to the brain. We developed a patient specific brain stimulation platform with a two-way feedback system, to synchronize single-pulse TMS with exoskeleton along with adaptive performance visual feedback, in real-time, for a focused neurorehabilitation strategy to voluntarily engage the patient in the brain stimulation process. Results: The novel TMS Synchronized Exoskeleton Feedback (TSEF) platform, controlled by the patient’s residual Electromyogram, simultaneously triggered exoskeleton movement and single-pulse TMS, once in ten seconds (0.1Hz). The TSEF platform was tested for a demonstration on 3 patients with different spasticity on Modified Ashworth Scale (MAS=1, 1+, 2) for one session each. Three patients completed their session in their own timing; patients with (more) spasticity tend to take (more) inter-trial intervals. A feasibility study of TSEF was performed for twenty sessions for 45 minutes/day. Post 20 sessions, an increase in ipsilesional cortical excitability was observed (Motor Evoked Potential increased by 48.5 μV at a decreased Resting Motor Threshold by 15.6%, with improvement in clinical scales relevant to the Fugl-Mayer Wrist/Hand joint (involved in training) by 2.6 units. This strategy could voluntarily engage the patient as suggested by this feasibility study and warrants further investigation on larger-cohort.